2017
DOI: 10.1007/s00414-017-1691-6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive examination of conventional and innovative body fluid identification approaches and DNA profiling of laundered blood- and saliva-stained pieces of cloths

Abstract: Body fluids like blood and saliva are commonly encountered during investigations of high volume crimes like homicides. The identification of the cellular origin and the composition of the trace can link suspects or victims to a certain crime scene and provide a probative value for criminal investigations. To erase all traces from the crime scene, perpetrators often wash away their traces. Characteristically, items that show exposed stains like blood are commonly cleaned or laundered to free them from potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 58 publications
2
13
0
Order By: Relevance
“…The transfer of blood specific mRNA has also been previously reported by van den Berge et al [35]. Samples washed without the addition of other clothes did not exhibit any transfer of mRNA, which is also consistent with several previous studies [19,34,35]. The blood miRNA target (miR-451a) was detected in all unstained cuttings, and transfer of the semen specific target (miR-891a) was observed in half of the unstained samples.…”
Section: Laundry Studysupporting
confidence: 90%
See 2 more Smart Citations
“…The transfer of blood specific mRNA has also been previously reported by van den Berge et al [35]. Samples washed without the addition of other clothes did not exhibit any transfer of mRNA, which is also consistent with several previous studies [19,34,35]. The blood miRNA target (miR-451a) was detected in all unstained cuttings, and transfer of the semen specific target (miR-891a) was observed in half of the unstained samples.…”
Section: Laundry Studysupporting
confidence: 90%
“…2). Previous studies [20,34] have also reported diminished visibility of bloodstains on materials washed at higher temperatures (60-95°C). The mRNA and miRNA results of the laundry study can be seen in Fig.…”
Section: Laundry Studymentioning
confidence: 79%
See 1 more Smart Citation
“…In contrast, van den Berge et al [104] found that the average persistence rates of DNA from both blood and saliva-stained cloths after washing were less than 0.001%, and the transfer of DNA from these stains onto the co-washed items was found to be extremely limited with only a very few alleles, if any, being detected. Whilst Kulstein and Wiegand [191] also obtained no reportable or informative DNA profiles from clean cloths washed with salivastained cloths, they found 52% of saliva-stained cloths gave reportable DNA profiles after washing. The reason for such different results between the studies is unclear, especially given that the starting volumes of blood and saliva in Kulstein and Wiegand's study were smaller than those used by van den Berge et al (20/100 µl versus 500/1000 µl).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…For example, DNA profiles from semen stains were found to still be retrievable after washing and also retrievable from other co-washed clothing as well as the washing machine drum [161,189]. Similarly, reportable and/or informative DNA profiles from blood tended to be obtained from washed blood-stained cloths and from co-washed clean cloths [190][191][192]. In contrast, van den Berge et al [104] found that the average persistence rates of DNA from both blood and saliva-stained cloths after washing were less than 0.001%, and the transfer of DNA from these stains onto the co-washed items was found to be extremely limited with only a very few alleles, if any, being detected.…”
Section: Accepted Manuscriptmentioning
confidence: 99%